The Physicochemical Properties of Butterfly Pea Flower (Clitoria ternatea L.) Extracts: Influence of Various Extraction Conditions - Sitompul, Johannes Nathanael; Martati, Erryana (The Journal of Experimental Life Science, 2025)
Butterfly pea flowers (Clitoria ternatea L.) have health benefits because they contain phenolic compounds, flavonoids, and anthocyanins, which act as antioxidants. There are few comparative studies on how the brewing temperature of butterfly pea flowers (hot, room, and cold temperatures) affects the release of antioxidants and anthocyanins. This study examined the effect of brewing methods on the physicochemical characteristics of butterfly pea flower extract. A nested experimental design was used, with brewing time nested within each brewing method. The brewing methods studied were hot brewing (HB) at 70°C for 5 and 15 minutes, room temperature (RT) brewing at 25-27°C for 3 and 6 hours, and cold brewing (CB) at 5-7°C for 12 and 24 hours. The color, pH, total anthocyanin content, and antioxidant activity were measured for the extract. The data obtained were statistically analyzed using ANOVA and Tukey's advanced test. The results showed that the brewing method significantly affected antioxidant activity but did not affect the total anthocyanin content, pH, or color. Brewing duration significantly influences all parameters except the color parameter b*. The best treatment of brewing methods for butterfly pea flowers was hot brewing for 15 minutes by simple additive weighting (SAW) method. The phenolic, flavonoid, alkaloid, and coumarin component groups made up the phytochemical composition of the butterfly pea flower extract.